EFEKTIVITAS KONSELING REALITAS UNTUK MENINGKATKAN MOTIVASI BELAJAR - Manja (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2019)
The purpose of this study was to determine whether reality counseling can increase learning motivation. This research is an experimental research with one group pre-test and post-test design. The subjects of this study were 10 students who have low learning motivation and meet several criteria in the research subject. Selection of research subjects based on the results of interviews with counseling teachers. Before and after treatment. The data analysis used the percentage descriptive data analysis technique and the Wilcoxon test. The results showed that the motivation to learn before getting reality counseling was included in the low criteria with a percentage of 48.2%. After receiving reality counseling, it increased to 63% with moderate criteria. Thus there was a positive change of 15.3%. The results of the calculation of the Wilcoxon test before and after getting treatment, obtained Zhitung = 2.20> Ztabel = 0 with a significance level of 5% so that it is stated that Ha is accepted. In other words, reality counseling can increase low learning motivation. The conclusion of this study is that learning motivation can be improved through reality counseling services.